Rabies antibody levels in pregnant women and their newborns after rabies post-exposure prophylaxis - Ahmad Fayaz; Susan Simani; Vida Fallahian; Ali Eslamifar; Mahboob Hazrati; Firoozeh Farahtaj; Nader Howaizi; Peivand Biglari (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2012)
Background: Rabies is a fatal infectious disease and rabies post-exposure prophylaxis is the method of choice for prevention of human rabies.Case series: We report rabies antibody levels in cord blood and also in serum of pregnant women who were bitten by suspected animals to rabies and were immunized by purified Vero cell rabies vaccine (PVRV) and Human Rabies immunoglobulin (HRIG) serum. During the years of 2007-2010, six pregnant women by the age range of 22-35 years were admitted in treatment and prevention of rabies center in Pasture institute of Iran, in Tehran. Among them two cases were at first trimester, one at second trimester and three at third trimester of conception. The interval between biting with delivery was 5-265 days (mean 121 days).Conclusion: Results of immunoglobulin illustrate that levels of rabies antibody in maternal sera with the fetus are not equal and uniform but it is proved that baby will find efficient immunity as well with minimum protective level of 0.5 IU/ml in all cases except a newborn whom had been born just 5 days after the mother's immunization and in a shorter time than the appropriate immunization of the mother who had received her second vaccination courses.